How Technostress Shapes Anxiety Levels in Learning Four Language Skills? Evidence from Thai Students - Chika Amanda Fauzi; Rakhmat Wahyudin Sagala (Journal of Social Research, 2026)
The rapid integration of digital technology in education has introduced new challenges, particularly for junior high school students learning English. Technostress, defined as the stress caused by difficulties in adapting to new technologies, has emerged as a significant factor affecting students' emotional responses in digital learning environments. This study aims to explore the relationship between technostress and language learning anxiety, focusing on Thai junior high school students. The research employs a quantitative explanatory design using Partial Least Squares Path Modeling (PLS-PM) to analyze how various dimensions of technostress, such as techno-anxiety, techno-overload, and techno-uncertainty, contribute to anxiety in learning English across four skills: speaking, listening, reading, and writing. The findings indicate a significant positive relationship between technostress and language learning anxiety, with techno-uncertainty and techno-anxiety identified as the most impactful stressors. The study highlights the need for educators to minimize platform switching, create error-friendly learning environments, and maintain consistent digital routines to reduce anxiety. The results provide practical insights for developing more emotionally supportive digital learning designs, ensuring that technology-based education is both effective and psychologically sustainable for young learners.